Wood Anatomy of Indian Shrubs of Euphorbiaceae S.L.: Identification, Ecological and Evolutionary Perspectives - Jangid, Prem Prakash; Gupta, Sangeeta (Indian Forester, 2017)
The present study deals with detailed wood microstructure of shrubs of the family Euphorbiaceae from India. Ten species belonging to 6 genera of Euphorbiaceae have been described on the basis of their detailed wood microstructure, salient diagnostic features and photomicrographs. An identification key based on wood anatomical features has been developed for the separation of the species. These species have quite different wood structure and are easily separable. However, these differences suggest unnatural classification of the family. The present study is useful in species identification and also reflecting ecological and evolutionary aspects.